(untitled) (International Journal of Islamic Business, 2022)
Indian Muslim (mamak) restaurant operators faced challenges to survive due to manpower shortage which affected its service to customers. Past studies related to restaurants often focused on customer satisfaction rather than employees who are supposedly the backbone of the company, of which, less attention given on the aspect of religiosity and motivation. Thus, the study aimed to analyze the effect of religiosity and motivation on employees’ job performance evidenced from mamak restaurants in Kuching, Sarawak, Malaysia. This survey included 145 employees of Mamak restaurants and employed quantitative approach for data collection. Regression analysis was employed to analyze the instrument and test the study hypotheses during the analysis procedures. The finding revealed that both religiosity and motivation have positive effect on job performance. It could be described that being able to perform ibadah means a lot to employees and by having the management provide motivation in the form of monetary or non-monetary could further boost their work productivity. This study also recommended that this area be expanded as it has yet been undertaken from the perspective of employees. This research adds to the theoretical knowledge by offering empirical support on the factors influencing employee performance improvement as well as managerial contribution for restaurant operators to take religious and motivational initiatives for the betterment of the business. Management should consider improvising employees’ compensational package that reflect their contributions to the company.